Analisis Efektivitas dan Laju Pertumbuhan Pajak Daerah serta Kontribusinya Terhadap Pendapatan Asli Daerah Di Kota Bogor Periode 2013-2017 - Secillia Herjanti; I Wayan Teg Teg (Institut Bisnis dan Informatika Kesatuan, 2020)
The existence of regional autonomy that applies in Indonesia, the autonomous region both provincial and district / city must be able to regulate and manage their own regions and are required to try to increase Regional Original Revenue (PAD) which has potential in the region one of which is in the collection of local taxes. Hotel Tax, Restaurant Tax and Entertainment Tax have the potential to increase PAD in Bogor City. The purpose of this study was to determine the level of effectiveness of hotel tax collection, restaurant tax and entertainment tax in the city of Bogor for the period 2013-2017, find out how much the growth rate of hotel taxes, restaurant tax and entertainment tax in the city of Bogor in the period 2013-2017 and how much the contribution of tax hotel, restaurant tax and entertainment tax on Regional Original Revenue (PAD) in Bogor City for the period 2013-2017. The method used in this research is descriptive qualitative method.The results of this study indicate that the effectiveness of hotel tax, restaurant tax and entertainment tax for the 2013-2017 period in the city of Bogor are included as very effective criteria with the effectiveness level of hotel tax collection, restaurant tax and entertainment that exceeds 100% each year. The average growth rate for hotel tax, restaurant tax and entertainment tax for the 2013-2017 period in Bogor City is as follows, 14.15%, 17.55% and 11.93%. The increase / decrease in the growth rate of hotel taxes, restaurant taxes and entertainment taxes each year is caused by several factors including the policies of the central government, the influence of the increase / decrease in the number of visitors who come, and the level of tourists visiting Bogor City. Meanwhile, the average contribution of hotel tax, restaurant tax and entertainment tax to PAD for the 2013-2017 period in the City was 8.58% with very less criteria, 11.50% with less criteria and 3.09% with very less criteria. The decrease in the contribution of hotel tax, restaurant tax and entertainment tax is influenced by the central government policy, the number of visitors and the significant increase in the realization of other regional tax revenues (BPHTB). Keywords: Local Revenue, Hotel Tax, Restaurant Tax, Entertainment Tax, Effectiveness, Growth Rate and Contribution.